Multiple Roles of Angiopoietin-Like 4 in Osteolytic Disease - Knowles, Helen J. (Frontiers in Endocrinology, 2017)
Hypoxia and the hypoxia-inducible transcription factor HIF drive pathological bone loss in conditions including rheumatoid arthritis, osteoarthritis, osteoporosis, primary bone tumours and bone metastatic cancer. There is therefore considerable interest in determining the function(s) of HIF-induced genes in these pathologies. Angiopoietin-like 4 (ANGPTL4) is an adipose-derived, HIF-1alpha- and PPARgamma-induced gene that was originally discovered as an endocrine and autocrine / paracrine regulator of lipid metabolism. Given the inverse relationship between bone adiposity and fracture risk, ANGPTL4 might be considered a good candidate for mediating the downstream effects of HIF-1alpha relevant to osteolytic disease. This review will consider the possible roles of ANGPTL4 in regulation of osteoclast-mediated bone resorption, cartilage degradation, angiogenesis and inflammation, focusing on results obtained in the study of rheumatoid arthritis. Possible roles in other musculoskeletal pathologies will also be discussed. This will highlight ANGPTL4 as a regulator of multiple disease processes which could represent a novel therapeutic target in osteolytic musculoskeletal disease.